Genetic Analyses of Mutations Contributing to Fluoroquinolone Resistance in Clinical Isolates of Streptococcus pneumoniae - Weigel, L. M. (American Society for Microbiology, 2001)
Twenty-one clinical isolates of Streptococcus pneumoniae showing reduced susceptibility or resistance to fluoroquinolones were characterized by serotype, antimicrobial susceptibility, and genetic analyses of the quinolone resistance-determining regions (QRDRs) of gyrA, gyrB, parC, and parE. Five strains were resistant to three or more classes of antimicrobial agents. In susceptibility profiles for gatifloxacin, gemifloxacin, levofloxacin, moxifloxacin, ofloxacin, sparfloxacin, and trovafloxacin, 14 isolates had intermediate- or high-level resistance to all fluoroquinolones tested except gemifloxacin (no breakpoints assigned). Fluoroquinolone resistance was not associated with serotype or with resistance to other antimicrobial agents. Mutations in the QRDRs of these isolates were more heterogeneous than those previously reported for mutants selected in vitro. Eight isolates had amino acid changes at sites other than ParC/S79 and GyrA/S81; several strains contained mutations in gyrB, parE, or both loci. Contributions to fluoroquinolone resistance by individual amino acid changes, including GyrB/E474K, ParE/E474K, and ParC/A63T, were confirmed by genetic transformation of S. pneumoniae R6. Mutations in gyrB were important for resistance to gatifloxacin but not moxifloxacin, and mutation of gyrA was associated with resistance to moxifloxacin but not gatifloxacin, suggesting differences in the drug-target interactions of the two 8-methoxyquinolones. The positions of amino acid changes within the four genes affected resistance more than did the total number of QRDR mutations. However, the effect of a specific mutation varied significantly depending on the agent tested. These data suggest that the heterogeneity of mutations will likely increase as pneumococci are exposed to novel fluoroquinolone structures, complicating the prediction of cross-resistance within this class of antimicrobial agents.